2002
DOI: 10.1590/s0103-50532002000300002
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Calix[4]arene and Aliphatic Amines: A Combined NMR, Spectrophotometric and Conductimetric Investigation

Abstract: As constantes relacionadas ao equilíbrio entre calix [4]areno e aminas alifáticas em acetonitrila foram medidas por métodos condutivimétrico e espectrométrico e as estruturas dos sais estudadas por espectroscopia de RMN. Em concentrações próximas a 10 -4 mol L -1 predominam os íons livres, enquanto que a 10 -2 mol L -1 aumenta a proporção de pares iônicos. Os valores das constantes para as reações ácido-base permitem avaliar o valor de pKa do calix[4]areno em acetonitrila, igual a 16,6 unidades de pKa. A análi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…[23,38] This can be attributed to a reduction in host symmetry, leading to poor packing, and which is a consequence of proton transfer from one phenolic hydroxyl to one of the amines, in accord with calixarene pK a values. [39][40][41] The X-ray data supports this, as only three of the phenolic oxygens are proton bearing, and excess electron density is found around one of the amino groups. The highly symmetrical and efficient packing schemes observed in 1:1 and 2:1 inclusion compounds are therefore not available in basic media.…”
Section: Resultsmentioning
confidence: 64%
“…[23,38] This can be attributed to a reduction in host symmetry, leading to poor packing, and which is a consequence of proton transfer from one phenolic hydroxyl to one of the amines, in accord with calixarene pK a values. [39][40][41] The X-ray data supports this, as only three of the phenolic oxygens are proton bearing, and excess electron density is found around one of the amino groups. The highly symmetrical and efficient packing schemes observed in 1:1 and 2:1 inclusion compounds are therefore not available in basic media.…”
Section: Resultsmentioning
confidence: 64%
“…This strong intramolecular H-bonding leads to pK a values for CAs being different from the monomeric units, 4,5 and the balance of the interaction between the guest molecule and either the benzene or the hydroxyl group sites is very subtle. For example, recent studies reported that the ''calix [4]arene(C4A)-aliphatic amine'' complex exists as the exo-complex in which a protonated amine is bound to C4A outside the cavity via the N + -HÁ Á ÁO À form, 6,7 though the complex was initially suggested to be the endo-complex.…”
Section: Introductionmentioning
confidence: 99%
“…Early values of pK a of calix [4]arene were obtained by Nachtigall using an indirect approach from titrations with amines as 16.6 in acetonitrile [15], that agrees with the high acidity of these compounds, when compared with the analogous phenols [16]. Machado showed that the values of pK a of phenols in acetonitrile and water displayed a linear relationship [17] (pK a (CH 3 CN) = 1.68 pK a (water) ?…”
Section: Calix[4]arene In Acetonitrilementioning
confidence: 63%